2006
DOI: 10.1007/s00411-006-0073-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic effects of low-dose radiation with different LET in human peripheral blood lymphocytes

Abstract: Chromosome damage and the spectrum of aberrations induced by low doses of gamma-irradiation, X-rays and accelerated carbon ions (195 MeV/u, LET 16.6 keV/microm) in peripheral blood lymphocytes of four donors were studied. G0-lymphocytes were exposed to 1-100 cGy, stimulated by PHA, and analyzed for chromosome aberrations at 48 h post-irradiation by the metaphase method. A complex nonlinear dose-effect dependence was observed over the range of 1 to 50 cGy. At 1-7 cGy, the cells showed the highest radiosensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Russian researchers found that the HRS/IRR could be observed by the anaphase method and micronucleus assay in X-ray using Chinese hamster V79 cells and human melanoma cells (27). Recently, they prompted a complex nonlinear dose-effect dependence in chromosome aberrations over the dose range of 1-50 cGy with different LETs in human peripheral blood lymphocytes, high yield of chromatid type aberrations was found at HRS dose range in both low and high LET radiations, which confirmed the idea that the molecular mechanisms that underlie the HRS phenotype may differ from the classical mechanisms of radiation-induced aberration formation, they proposed that there were possibly common mechanisms underlying all low-dose phenomena (2). Our data supported that there was the occurrence of HRS/IRR for HPRT mutation frequency in GM cells exposed to carbon ions (Fig.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Russian researchers found that the HRS/IRR could be observed by the anaphase method and micronucleus assay in X-ray using Chinese hamster V79 cells and human melanoma cells (27). Recently, they prompted a complex nonlinear dose-effect dependence in chromosome aberrations over the dose range of 1-50 cGy with different LETs in human peripheral blood lymphocytes, high yield of chromatid type aberrations was found at HRS dose range in both low and high LET radiations, which confirmed the idea that the molecular mechanisms that underlie the HRS phenotype may differ from the classical mechanisms of radiation-induced aberration formation, they proposed that there were possibly common mechanisms underlying all low-dose phenomena (2). Our data supported that there was the occurrence of HRS/IRR for HPRT mutation frequency in GM cells exposed to carbon ions (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Although the intrinsic mechanisms and targets of low-dose effects are not fully clear, large amount of data indicate that below 0.5 Gy, certain effects are not quantitatively related to the dose and that fundamentally different processes are involved in the cells' response to ionizing radiation (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous reports confirmed the lack of linearity in radiation dose responses at low doses for such end points as micronuclei ( Słonina et al . 2006 ), chromosomal aberrations ( Nasonova et al . 2006 ), cellular clonogenic survival ( Marples and Joiner 1993 ) and others.…”
Section: Discussionmentioning
confidence: 99%
“…It could be attributable to the fact that the system responded to the X-rays with an excess of damage for the doses 0.1 and 0.25 Gy, recalling a possibility of a kind of low-dose HRS, and actually such an occurrence has been reported with classical non-molecular cytogenetic techniques on rodent and human cells (Tsoulou et al, 2001; Nasonova et al, 2006). Nevertheless the regression functions without low-dose HRS-like correction were preferred because without further experimental points far from HRS peak a conclusive evidence is missing, and secondly for practical reasons of calculation of the thresholds doses for the detectable damage induction.…”
Section: Discussionmentioning
confidence: 91%